Dampak Teknologi Artificial Intelligent dan Cara Menghadapi Blockchain Technology dalam Perspektif Akuntansi - Sevita Sari Dewi; Eko Suyono (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
The development of Artificial Intelligence technology is changed the accounting profession. This paper provides a comprehensive overview of recent development in Artificial Intelligence, Big Data and Machine Learning use in business practices in the accounting profession worldwide. The paper explores the evolution of the accounting profession following recent technological developments and assesses the impact of these developments in the future. The challenges and opportunities posed by Artificial Intelligence relating to accounting professionals and the process of accounting education. This research uses a normative juridical approach with a literature study of secondary data. This paper provides an overview of how accounting educators and professionals respond to these technological developments and provides further discussion on what accounting profession, institutions and graduates should do to face the challenges of change caused by technological developments. This research aims to describe the development and system of blockchain, identify potensial uses, analyze internal and external factors, and identify how accountants face blockchain disruption. The method use is descriptive qualitative. Data was obtained through interviews and literature studies. This research shows that blockchain technology has potential implementation in accounting, auditing, finance, supply chain, and public sector. Practitioners and academics need to pay attention to the curriculum and framework related to blockchain implementation, from one set of skills, and the current role of accountants is as business advisors or consultants and not as counters.